2011
DOI: 10.1002/csr.267
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on corporate social responsibility: A study in capturing public confidence

Abstract: This study examines the perceptions and expectations of the stakeholders of corporate social responsibility (CSR) disclosure practices in Indonesia based on CSR-related items. Using survey data on CSR disclosures in Indonesia, this study applies factor analysis to identify relationships among nine CSR characteristics. The statistical results indicate that the relationship between CSR contents, incentives, format, public confi dence, and impact on investment decisions is positively and directly related. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 24 publications
2
58
0
3
Order By: Relevance
“…For instance, research has shown that older people's concern about CSR is greater than that of younger people (Shauki 2011), and that older employees are more motivated than younger employees by intrinsically rewarding job features-like knowing that what the organization does is ethically correct (Inceoglu et al 2012). However, these studies did not address the hypothesis that the relation between CSR and employees' work-related attitudes (such as job satisfaction) is moderated by employee age.…”
Section: The Role Of Employee Age In Effects Of Csrmentioning
confidence: 99%
“…For instance, research has shown that older people's concern about CSR is greater than that of younger people (Shauki 2011), and that older employees are more motivated than younger employees by intrinsically rewarding job features-like knowing that what the organization does is ethically correct (Inceoglu et al 2012). However, these studies did not address the hypothesis that the relation between CSR and employees' work-related attitudes (such as job satisfaction) is moderated by employee age.…”
Section: The Role Of Employee Age In Effects Of Csrmentioning
confidence: 99%
“…De esta forma, las empresas han pasado de desempeñar únicamente un rol económico, a ejercer una función complementaria de carácter social y medioambiental, enfocada a lograr una mejora en la calidad de vida y bienestar de las personas y grupos involucrados en sus operaciones (Barreto & Baden-Füller, 2006;Scherer & Palazzo, 2011). Esta triple consideración de los impactos económicos, sociales y medioambientales en los resultados organizativos -triple bottom line- (Elkington, 1998), se refleja en la creciente elaboración de informes de sostenibilidad por parte de las compañías, que tratan con este proceso de justificar y proporcionar una mayor transparencia de sus acciones antes sus diversos grupos de interés (Shauki, 2011).…”
Section: Revisión De La Literatura Y Marco Teóricounclassified
“…Regarding to the provision of environmental services, the issue of Undang-undang Nomor 40 tahun 2007 tentang Perseroan Terbatas (Act No.40/2007 on Limited Corporation) which states that it is the duty for the organizations to allocate 1% to 3% of funds for the Corporate Social Responsibility, is an opportunity for the pulbic accountants to do auditing towards the implementation of this law (KeMenKuHam, 2007;Shauki, 2011). Therefore, public accountants need binding regulation, which can be taken as the standards in providing the accounting information (Lodhia, 2003;Medley, 1997).…”
Section: The Accounting Professional Bodies' Role In Environmental Awmentioning
confidence: 99%
“…Although the participants feel skeptical about the government's commitment, most of them as the boards of accounting profession bodies expect supports and enforcement from the government to encourage the socialization of environmental awareness among the accountants. One example happening in China proves that enforcement from Chinese government can change the mindset of business people and accountants (Yee, 2009 (Shauki, 2011). Yet, this is still not enough to enforce the improvement of environmental awareness.…”
Section: Factors Affecting Environmental Awarenessmentioning
confidence: 99%
See 1 more Smart Citation